Sīrat-i Ashraf : yaʻnī, savāniḥʻumrī Ḥakīmulummat Ḥaz̤rat Maulānā Ashraf ʻAlī Thānvī - ʻAbdurraḥmān Ḵẖān, 1913- (Shaiḵẖ Akaiḍaimī, 1977)
Hagiography of Ashraf Ali Thanvi, 1863-1943, eminent Muslim religious scholar of Deoband, India.